Neologia lexical: um estudo da fala e da vida de bilíngües português-fala dialetal italiana (RCI-RS) - Alberti, Janaina Ramos (My University, 2014)
The present study explores the relation between lexis and culture through the analysis of neologisms by borrowing (Haugen, 1972; Guilbert, 1975) in lexical fields. The neologisms are verified in Portuguese in the speech of Italian descendants who live in a rural area of Caxias do Sul, RS, Brazil. The data were collected from 24 sociolinguistic interviews of the BDSer corpus (UCS - DELE - Mestrado em Letras e Cultura Regional). The 42 units which were analyzed are borrowings from Italian dialects still spoken in the area. To establish the relation between cultural practices and lexical innovation, the data are structured in lexical fields which are, in turn, integrated in a network format, according to Biderman (1981). The research implied an ethnographical study in order to make possible the identification of social practices associated to the use of the units, justifying, thus, the organization of the lexical fields. The data were divided into two semantic networks which represent the basic cultural equipment of Bevilácqua, one of the studied communities.
Este estudo explora a relação existente entre léxico e cultura por meio da análise em campos léxicos de neologismos verificados na língua portuguesa falada por bilíngües português-fala dialetal italiana (RCI-RS). Os dados foram extraídos de 24 entrevistas sociolingüísticas do BDSer realizadas na zona rural de Caxias do Sul, mais especificamente nas comunidades de Bevilácqua, São Braz e Santo Homobom. Foram considerados 42 neologismos por empréstimo - segundo conjugação da classificação proposta por Haugen (1972) e por Guilbert (1975) - ocorridos em unidades lexicais simples. Para estabelecer a relação entre práticas culturais e ampliação lexical os dados foram estruturados em campos léxicos, conforme Biderman (1981), integrados no formato de rede. Essa estruturação exigiu a realização de estudo etnográfico para que se identificasse o quadro de práticas sociais de que faz parte o emprego das unidades, justificando, dessa forma, a organização dos campos léxicos. Após a realização do estudo etnográfico, os dados foram divididos em duas redes semânticas representativas do equipamento cultural básico da comunidade de Bevilácqua.
Keywords: Sociolingüística e dialetologia; Neologia por empréstimo; Unidade lexical simples; Cultura regional; Campo léxico; Rede semântica; Neology; Borrowings; Lexical fields; Social practices; Semantic network